Statistical learning using neural networks : a guide for statisticians and data scientists /: a guide for statisticians and data scientists. (2020) - Pereira, Basilio de Bragança; Rao, C. Radhakrishna (Calyampudi Radhakrishna), 1920-; Borges de Oliveira, Fabio
No abstract available